Molecular dynamics and ab-initio modelling of ring-like classical Coulomb clusters and cr-based molecular magnet - Tomecka, Daria M. (My University, 2011)
The following thesis is devoted to determination of structural, dynamical and new melting properties of twodimensional classical Coulomb clusters and electronic and magnetic properties of chromium-based molecular magnets. The two-dimensional Coulomb clusters are studied with the use of molecular dynamics and Monte Carlo methods, and Cr-based systems with the use of abinitio method. In the first part of the following thesis we investigated the geometrical structures and the motion of uniformly and non-uniformly charged particles at low temperatures before the radial and angular melting sets in. In the following thesis the reader will find much richer than the hitherto two-step approach to the melting process of 2D classical clusters. The relation between magic number configurations, local radial melting of subshells and the intershell rotation is analyzed. Additionally the ground state and metastable configurations for different charges as well as the new melting scenarios are determined. In the second part of this thesis, for the first time we proposed 1D chain models of Cr8 antiferromagnetic molecular ring.The chain models discussed here are devised to mimic the properties of Cr8 molecule and significantly simplify computational complexity. Detailed investigations of electronic and magnetic properties of created models of Cr8 molecule are presented.
Wydział Fizyki: Zakład Fizyki Komputerowej; European Institute of Molecular Magnetism
Keywords: 2d classical Coulomb clusters; melting; molecular dynamics; cr-based molecular; ab-initio/dft modelling